Dissecting Cultural Identity Construction among EFL Learners: Voices from the Periphery - Prasatyo, Bayu Andika; Amaliah, Amaliah (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
This paper investigates how English as a foreign language (EFL) learners construct their cultural identity and how globalisation influences this construction. It also explores studies on globalisation and English language learning in EFL contexts, focusing on students living in peripheral areas. 44 EFL learners aged between 18 and 25 years old were the participants in the study. The study utilized a mixed-method descriptive approach as the foundational framework for this research. The quantitative data consists of questionnaires and semi-structured interviews. They were collected using open-ended questions and then supplemented with semi-structured questions. The qualitative approach is further supported by previous research on cultural identity, such as cultural identity projection analysis and the influence of globalization on education. The study revealed that EFL English learners express their cultural identity through various aspects, such as their interactions with others, self-perception as students in a globalized world, and the impact of globalization on their identity. Students' cultural identity in peripheral areas is influenced by nationality, lifestyle, language, local community, education, cultural shock, mass media, and political beliefs. These elements influence the construction of an individual's cultural identity